Tofacitinib and analogs as inhibitors of the histone kinase PRK1 (PKN1). (September 2016) - Ostrovskyi, Dmytro; Rumpf, Tobias; Eib, Julia; Lumbroso, Alexandre; Slynko, Inna; Klaeger, Susan; Heinzlmeir, Stephanie; Forster, Michael; Gehringer, Matthias; Pfaffenrot, Ellen; Bauer, Silke Mona; Schmidtkunz, Karin; et al.
Aim: The histone kinase PRK1 has been identified as a potential target to combat prostate cancer but selective PRK1 inhibitors are lacking. The US FDA -approved JAK1–3 inhibitor tofacitinib also potently inhibits PRK1 in vitro .Results: We show that tofacitinib also inhibits PRK1 in a cellular setting. Using tofacitinib as a starting point for structure–activity relationship studies, we identified a more potent and another more selective PRK1 inhibitor compared with tofacitinib. Furthermore, we found two potential PRK1/JAK3-selectivity hotspots.Conclusion: The identified inhibitors and the selectivity hotspots lay the basis for the development of selective PRK1 inhibitors. The identification of PRK1, but also of other cellular tofacitinib targets, has implications on its clinical use and on future development of tofacitinib-like JAK inhibitors.